Neurophilosophy or Philosophy of Neuroscience? What Neuroscience and Philosophy can and can´t do for each other - Jungert, Michael (The Human Sciences after the Decade of the Brain. Perspectives on the Neuro-Turn in the Social Sciences and the Humanities, 2017)
Ever since the rise of modern neuroscience, there has been a controversial discussion about its potential influence on topics that were traditionally seen as part of the domain of social sciences and humanities. At present, the formation of a large number of neuro-hyphenated disciplines such as neuro-theology, neuro-psychoanalysis, or neuro-economics shows the appeal of applying neuroscientific methods to traditional scientific fields. In philosophy, two distinct ways of dealing with the problems and prospects of neuroscience have been developed: While the philosophy of neuroscience tries to apply methods and classical approaches from the philosophy of science to neuroscience, so-called neurophilosophy takes a different approach by applying neuroscientific findings to classical philosophical issues. I evaluate the premises and chances of both approaches by discussing their methods, theoretical assumptions, and explanatory aims. Finally, I will look into neurophilosophy´s claim to integrate neuroscientific findings into philosophical theory by analyzing the relation between memory and personal identity.
Keywords: neurophilosophy; philosophy of neuroscience; autobiographical memory; personal identity; philosophical method; interdisciplinarity